Ineffective Homeschooling in a Child with a Learning Disability. Issue 2 (February 2019) - Quist, Megan; Chopp, Debra; Wilson, Camille M.; Radesky, Jenny
Abstract : CASE: Charles is a 10-year-old African-American male who presents to the Developmental Behavioral Pediatrics Clinic for evaluation of his learning. His primary care provider (PCP) was concerned that his developmental delays were negatively affecting his ability to engage in his homeschooling curriculum and also that his mother seemed unaware of the severity of his delays. Neuropsychological evaluation had been recommended by the PCP several times in the past, but the family declined. At one point, the PCP had considered potential child protective services (CPS) referral for medical neglect because of missed appointments and lack of follow-through on recommendations, which motivated the parent to bring him to this appointment. Medical history was significant for failure to thrive and hypotonia in infancy. Charles received physical therapy through early childhood for hypotonia and motor coordination deficits. His mother removed him from public school and initiated homeschooling in kindergarten after he suffered a dental injury at recess of which she was not notified. The current homeschooling (fourth grade) approach was described as "off and on" activities for 3 hours daily. His mother acknowledged that she struggled to get him to participate as he preferred using the computer and tablet rather than doing school work, and they also argued regularly about his impulsive eating. The patient's mother also described her own medical conditions that contributed to a high degree of stress and fatigue, which she felt made homeschooling more difficult. On examination, the patient was obese and had widely set, almond-shaped eyes; a wide-based gait; an immature pencil grasp; and a mild truncal and appendicular hypotonia. Performance on the Kaufman Brief Intelligence Test, second edition, was below average for the verbal scale (78) and low average for the nonverbal scale (89). On the Wechsler Individualized Achievement Test, third edition, he was unable to perform any multiplication, could not write his own last name (was practicing tracing at home per maternal report), and read at a below first-grade reading level (standardized scores could not be calculated). His conversations with the examiner were mainly limited to the topic of video games. He spoke in short sentences with approximately 85% intelligibility but with coordinated gaze. He appeared mentally exhausted as testing progressed. Feedback to the parent included concern for a learning disability possibly associated with a genetic condition such as Prader-Willi syndrome (because of the history of hypotonia and impulsive eating), and genetic testing was recommended. Because of Charles' difficulty accessing the homeschool curriculum, a special education evaluation through the local public school district was also recommended, but his mother resisted, stating that she felt public special education "keeps children like him down" by focusing primarily on African-American children and stigmatizing their differences. The mother does not return phone calls made 1 month later to follow-up on considering a special education evaluation, and team members raise concern about medical neglect. What would you do next?